2016
DOI: 10.3390/ma9100855
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of CdSe Quantum Dots Using Fusarium oxysporum

Abstract: CdSe quantum dots are often used in industry as fluorescent materials. In this study, CdSe quantum dots were synthesized using Fusarium oxysporum. The cadmium and selenium concentration, pH, and temperature for the culture of F. oxysporum (Fusarium oxysporum) were optimized for the synthesis, and the CdSe quantum dots obtained from the mycelial cells of F. oxysporum were observed by transmission electron microscopy. Ultra-thin sections of F. oxysporum showed that the CdSe quantum dots were precipitated in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…Almeida et al (2017) also demonstrated the presence of amide I and II and aromatic groups in the ltrate of F. oxysporum, which they had applied to bio-synthesize silver NPs [24]. Yamaguchi et al (2016) observed that after production of biogenic CdSe quantum dots by F. oxysporum, in the superoxide evaluation, superoxide dismutase (SOD) in the cytoplasm decreased. They attributed these changes to the creation of CdSe quantum dots in F. oxysporum [25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Almeida et al (2017) also demonstrated the presence of amide I and II and aromatic groups in the ltrate of F. oxysporum, which they had applied to bio-synthesize silver NPs [24]. Yamaguchi et al (2016) observed that after production of biogenic CdSe quantum dots by F. oxysporum, in the superoxide evaluation, superoxide dismutase (SOD) in the cytoplasm decreased. They attributed these changes to the creation of CdSe quantum dots in F. oxysporum [25].…”
Section: Resultsmentioning
confidence: 99%
“…Yamaguchi et al (2016) observed that after production of biogenic CdSe quantum dots by F. oxysporum, in the superoxide evaluation, superoxide dismutase (SOD) in the cytoplasm decreased. They attributed these changes to the creation of CdSe quantum dots in F. oxysporum [25]. Peaks around 600 to 650 and at 1550 in FTIR could be attributed to sul de compounds according to [18,19], while EDX analysis of the NPs approved the existence of selenium and sulfur spectral peaks ( Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…The extracellular biosynthesis of various QDs using different species of fungus has been reported by several teams. For instance, F. oxysporum was used to produce ZnS QDs [ 151 ], CdTe QDs [ 152 ] and CdSe QDs [ 153 , 154 ]. On the other hand, the biomass of Phanerochaete chrysosporium [ 155 ] and Trametes versicolor [ 156 ] produces CdS QDs, Aspergilus flavus [ 157 ] synthesizes ZnS QDs and Helminthosporum solani yields CdSe QDs [ 158 ].…”
Section: In Vivo Biosynthesis Of Inorganic Nanomaterials Using Funmentioning
confidence: 99%
“…Sheikholeslami et al [17] examined nanoparticle transportation under the impact of thermal radiation. In recent decades, various researchers have published papers on heat transfer [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%